The aims of argument : - Crusius, Timothy W. (McGraw-Hill, 2003)
The Aims of Argument is a process-oriented introduction to argumentation with unique coverage of the aims, or purposes, of argument - to inquire, to convince, to persuade, and to mediate. In contrast to other approaches, the focus on aims provides rhetorical context that helps students write, as well as read, arguments.